Konstantynopol w "Kronice" Marcellina Komesa - Leszka, Mirosław J. (Vox Patrum, 2008)
Marcellinus’ Chronicie certainly belongs to the canon if its literary genre and as such it has been analyzed by scholars. It seems though, that it can also be looked at as a record of some observations of the life of a metropolis, done by its long-standing inhabitant. The inventory of issues picked-up by Marcellinus is not accidental and does not only serve a more or (mostly) less detailed description of the history of the Empire, but also reflects, at least to some extent, the Constantinopolitan microcosm. The chronicler reveals the problems that might be interesting to an inhabitant of the City, which were important to him and which he had to cope with. A Constantinopolitan of the lst half of 6th century was someone who had to live in the times of unrest. He was a witness to freąuent riots and disturbances, either by ordinary hooligans, members of circus factions, or those arising from the resistance against unpopular rulers (e.g. Anastasios), which sometimes led to usurpation attempts. He observed both cruel struggles and cruel repressions following them. It seems that Marcellinus respected Constantinople and was aware of living in an unusual place. His relations with the City may have been strong and emotional, which can be proved by the content of the Chronicie, fuli of Constantinopolitan threads, as well as by the fact that he dedicated part of his lost work Description of the City of Constantinople and of Jerusalem to it.